Pulmonary Hypertension Related to Left-Sided Cardiac Pathology - Todd L. Kiefer; Thomas M. Bashore (Pulmonary Medicine)
Pulmonary hypertension (PH) is the end result of a variety of diverse pathologic processes. The chronic elevation in pulmonary artery pressure often leads to right ventricular pressure overload and subsequent right ventricular failure. In patients with left-sided cardiac disease, PH is quite common and associated with increased morbidity and mortality. This article will review the literature as it pertains to the epidemiology, pathogenesis, and diagnosis of PH related to aortic valve disease, mitral valve disease, left ventricular systolic and diastolic dysfunction, and pulmonary veno-occlusive disease. Moreover, therapeutic strategies, which focus on treating the underlying cardiac pathology will be discussed.